E-FCNN Based Electric Power Inspection Image Enhancement - Wanrong BAI; Xun ZHANG; Xiaoqin ZHU; Jixiang LIU; Qiyu CHENG; Yan ZHAO; Jie SHAO (Zhongguo dianli)
For UAV patrol of transmission lines and robot inspection of unattended substations, low image resolution is one of the main problems due to long shooting distance or machine shaking. In order to solve this problem, we propose an edge-aware feedback convolutional neural network (E-FCNN), which not only adds Resnet blocks and feedback mechanism to the conventional super-resolution network to strengthen the ability of feature extraction, but also adds texture information to the edge-aware branch to enhance the image detail. Extensive experiments show that the proposed algorithm is superior to other existing algorithms, both in subjective visual quality and objective evaluation indexes such as peak signal-to-noise ratio. Practically, the proposed algorithm can improve the accuracy of insulator detection in UAV transmission line inspection.